Peran Manajemen Pemasaran Dalam Meningkatkan Daya Tarik Wisata The Lodge, Lembang (International Forum of Researchers and Lecturers, 2024)
The Lodge Maribaya is a beautiful tourist spot, which offers between natural and artificially created places with backdrops of pine forests for thousands of tourists to come during the weekend. However, the scope of study on marketing management could spiral into more interesting aspects of the field, which penetrate effective and sustainable marketing management. The method used in this research is qualitative methods (library research). According to the result of the research, it revealed that management plays a very significant role in enhancing the tourist’s appeal to the tourist destination of The Lodge Maribaya. Marketing management includes aspects of market segmentation, product development for tourism, promotion and communication, visitor services and experiences, and creation of a brand image.